Local Government Risk Assessment: The Effect of Government Type on Credit Rating Decisions in Texas. (June 2016) - Greer, Robert A.
Abstract : In consideration of increased levels of debt issued by special purpose local governments, this study explores the relationship between local government type and credit rating decisions. Investors use credit ratings as a signal for default risk, and risk level is a function of local economic base including service responsibilities and revenue sources. Governmental functions and economic bases vary across local government types which affect credit rating decisions. Specifically, special purpose governments have more limited responsibilities and revenue sources compared to general purpose governments. To model the decision of agency selection a multivariate probit model is estimated using bond deals from six different types of local governments in Texas. Findings suggest differences among general purpose and special purpose local governments. This supports the hypothesis that economic base affects credit rating decisions. Results indicate that credit rating agencies evaluate and weight information differently, and that local governments chose rating agencies in response.